Studi Persepsi Pengguna Angkutan On-Line dan Konvensional Terhadap Kualitas Infrastruktur Jalan di Kota Palu (Studi Kasus: Kecamatan Palu Selatan) - Karlina Ntaba (Universitas Kristen Indonesia Paulus, 2025)
Palu City, the administrative center of Central Sulawesi Province, has experienced rapid development in various aspects, including an increase in population and community mobility. These changes have resulted in an increased need for efficient and accessible transportation. Before the advent of app-based transportation, people still relied heavily on conventional public transportation as their primary mode of transportation. However, with the advent of on-line transportation services such as Gojek, Grab, and Maxim, people's mobility patterns have begun to change significantly. This study aims to determine the factors influencing transportation mode choice and the perceptions of on-line and conventional transportation users regarding the quality of road infrastructure in Palu City. The method used was a field survey with questionnaires and quantitative data analysis of 100 respondents. The results showed that people predominantly chose on-line transportation over conventional transportation. The main factors influencing this choice include service quality (90.82%), transparent and affordable fares (91.53%), ease of access (88.71%), and shorter travel time (86.82%). In addition, the presence of on-line motorcycle taxis has had a significant impact on reducing the number of passengers and the income of public transportation drivers. Of the total respondents, 85% chose to use on-line motorcycle taxis, while only 15% still used public transportation (angkot). In conclusion, the presence of on-line transportation has significantly influenced changes in the behavior of Palu City residents in choosing their mode of transportation. In addition to increasing efficiency and comfort, this situation also requires improvements in the quality of road infrastructure and adjustments to transportation policies to maintain a balance between on-line and conventional modes of transportation.